PSYCHOLOGICAL FACTORS OF OCCUPATIONAL BURNOUT OF IT PROFESSIONALS DURING MILITARY CONFLICT - Алексєєва, Іванна; Демченко, Наталія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article examines the psychological factors of professional burnout of IT specialists during military conflicts. The key factor in the development of professional burnout is stress, which depletes a person's physical and emotional resources. This causes cognitive impairment, emotional exhaustion and depression. The purpose of the study is to assess the impact of psychological factors, such as anxiety, stress and depressive manifestations that arise during military conflicts, on the level of professional burnout of IT specialists in different regions of Ukraine. To solve the tasks set, the following research methods were used: theoretical methods - analysis, systematization of theoretical approaches and generalization of research results; empirical methods - Hospital Anxiety and Depression Scale (HADS); Perceived Stress Scale (PSS); Diagnostics of professional burnout (Maslach, Jackson in the adaptation of Vodop'yanova) methods of mathematical statistics: Spearman's correlation. Results. Thanks to theoretical analysis, the main concepts and approaches to understanding professional burnout were investigated, which allowed us to identify key psychological factors, such as anxiety, stress, and depressive manifestations. Correlation analysis revealed significant relationships between the level of anxiety and emotional exhaustion, as well as between depressive manifestations and depersonalization. Such results indicate a close relationship between the mental state of IT specialists and their effectiveness. Conclusions. Based on the obtained data of statistical analysis, relationships were found between psychological factors and the intensity of professional burnout manifestations. Comparison of the obtained data between different regions of Ukraine was especially valuable. In particular, it was empirically confirmed that IT specialists in Dnipro demonstrate higher rates of anxiety, stress, and burnout compared to specialists from Kyiv. The result confirms that proximity to zones of active military operations has a significant impact on the psychological state of specialists. Key words: military conflict; depressive manifestations; IT professionals; professional burnout; psychological well-being; psychological factors; stress anxiety.